2019
DOI: 10.1136/tobaccocontrol-2019-055260
|View full text |Cite
|
Sign up to set email alerts
|

See you in court: obstacles to enforcing the ban on electronic cigarette flavours and marketing in Finland

Abstract: The aim of Finnish tobacco policy is to end the use of tobacco and other nicotine-containing products by 2030. Towards that end, the regulation of electronic cigarettes (e-cigarettes) in Finland is stricter than that in other European Union (EU) countries, including a ban on characterising flavours in e-cigarette liquids as well as on marketing e-cigarettes. This article describes the e-cigarette market, its regulation and the challenges faced in enforcing regulations in Finland. The materials used for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The Tobacco Act 2016 prohibits the sale and distribution of e-cigarettes to minors, online sales of e-cigarettes, flavouring agents that 'smell or taste other than one of tobacco' [27], and the use of e-cigarette anywhere tobacco cigarettes have been banned [27,28]. The legislation also prohibits the marketing and advertising of e-cigarettes, as well as the use of misleading claims [27,28]. Moreover, manufacturers are required to include appropriate labelling and health warnings on e-cigarette packages [28].…”
Section: Regulation Of E-cigarettes In Finlandmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tobacco Act 2016 prohibits the sale and distribution of e-cigarettes to minors, online sales of e-cigarettes, flavouring agents that 'smell or taste other than one of tobacco' [27], and the use of e-cigarette anywhere tobacco cigarettes have been banned [27,28]. The legislation also prohibits the marketing and advertising of e-cigarettes, as well as the use of misleading claims [27,28]. Moreover, manufacturers are required to include appropriate labelling and health warnings on e-cigarette packages [28].…”
Section: Regulation Of E-cigarettes In Finlandmentioning
confidence: 99%
“…The Tobacco Act 2016 also subjects e-cigarette solutions to excise duty [27]. A number of studies have demonstrated that an increase in e-cigarette prices is directly related to a decline in e-cigarette sales [29,30].…”
Section: Regulation Of E-cigarettes In Finlandmentioning
confidence: 99%
“…The ENDS/ENNDS prohibition in Brazil was motivated to prevent the population consuming a product whose safety and benefits were not yet confirmed, and, thus, the benefits of the prohibition are considered to outweigh the profits of sales of these products in the country 29 . Furthermore, with an abundance and variety of ENDS/ENNDS products, including e-liquid, available in the market, countries might encounter difficulties in formulating an effective regulation to assess the products under scrutiny 30 . As exemplified by Finland, the country’s policy on prohibition of characterising flavours in e-cigarette liquids and e-cigarette marketing was strongly challenged by e-cigarette businesses due to limited resources for tobacco control to expand in scope and the reluctance of the e-cigarettes industry to comply with the regulations 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with an abundance and variety of ENDS/ENNDS products, including e-liquid, available in the market, countries might encounter difficulties in formulating an effective regulation to assess the products under scrutiny 30 . As exemplified by Finland, the country’s policy on prohibition of characterising flavours in e-cigarette liquids and e-cigarette marketing was strongly challenged by e-cigarette businesses due to limited resources for tobacco control to expand in scope and the reluctance of the e-cigarettes industry to comply with the regulations 30 . Therefore, a total prohibition of ENDS/ENNDS products is deemed justified, given the potential loopholes present in complicated ENDS/ENNDS regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation